(untitled) (Ameghiniana, 2020)
We present the first record of the family Histeridae in late Pleistocene deposits in Chilean Northwestern Patagonia, based on fossil of a single elytron, registered at the Pilauco archaeo-paleontological site in Los Lagos Chilean region. We describe the fossil remain and discuss the paleoecology of the fossil related to the climate, fauna, and early human occupation context of the Pleistocene-Holocene transition.